Can investment in microfinance funds improve risk-return characteristics of a portfolio? - Janda, Karel; Rausser, Gordon; Svárovská, Barbora (Technological and Economic Development of Economy, 2014)
This article is concerned with contribution of microfinance investment funds to a sustainable financial portfolio. With regard to the dependence of microfinance funds’ returns on the performance of stock and fixed income markets in developed and emerging economies we find slightly negative correlation when measured by the portfolio beta measure. Our regression analysis confirms that returns on investment in microfinance investment funds exceed the returns on the market portfolio. This result together with reported near-to-zero beta estimates as a proxy for the systematic risk may be taken to be a clear financial advantage of an inclusion of microfinance assets in a portfolio compared to pure stock or bond portfolios. The results based on CAPM beta and Jensen’s alpha are confirmed by mean-variance spanning test. We show that the socially responsible investors may invest into microfinance without sacrifice with respect to pure financial indicators. First published online: 28 Jan 2014